Changes in the hospital care following European Working Time Directive with special reference to the craft specialties. (1st June 2011) - Cuschieri, Alfred; Turchetti, Giuseppe
The revised European Working Time Directive (EWTD) for doctors has changed hospital care delivery from the on call to the shift or rota system. Despite its potential benefits, it has major staff resource and cost implications and requires drastic changes in training of all hospital specialists, but especially those in the craft specialties. Inevitably, training of specialists has changed from being apprentice-based to competence-based. The impact of this change is crucial in the craft specialties such as surgery, where proficiency in execution of operations is crucial to patient outcome. Hence, several changes are needed to address this problem: more flexible curriculum, expansion in consultant numbers (consultant driven health service), improvement of the quality of training including establishment of dedicated training operating lists, supplemented by the establishment of skills laboratories in all training hospitals or regional training centres with ready access by trainees for both component and procedure-related skills.